2012
DOI: 10.1093/eurpub/cks026
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional screening in a population-based cohort of community-dwelling older people

Abstract: Being at risk of malnutrition was common among community-dwelling older people. Problems with mouth, IADL and cognitive impairments were linked to possible nutritional risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
57
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 28 publications
7
57
0
11
Order By: Relevance
“…Also, no serious pain or stiffness in muscles and joints, much interest shown from others, no psychological distress, no weekly use of analgesics, hypnotics, tranquilisers or antidepressants, no fall last year, and weekly commitment to light physical activity were closely linked with FA. The finding that intake of potatoes and vegetables were linked with FA are in line with findings of independent walking ability being inversely associated with malnutrition [15]. Furthermore, except for the higher total serum cholesterol in functionally able men, the anthropometric measurements and serum analyses indicate a healthier metabolism [16] and higher level of physical fitness [17] among the functionally able women and men than among those with functional limitations.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Also, no serious pain or stiffness in muscles and joints, much interest shown from others, no psychological distress, no weekly use of analgesics, hypnotics, tranquilisers or antidepressants, no fall last year, and weekly commitment to light physical activity were closely linked with FA. The finding that intake of potatoes and vegetables were linked with FA are in line with findings of independent walking ability being inversely associated with malnutrition [15]. Furthermore, except for the higher total serum cholesterol in functionally able men, the anthropometric measurements and serum analyses indicate a healthier metabolism [16] and higher level of physical fitness [17] among the functionally able women and men than among those with functional limitations.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, except for the higher total serum cholesterol in functionally able men, the anthropometric measurements and serum analyses indicate a healthier metabolism [16] and higher level of physical fitness [17] among the functionally able women and men than among those with functional limitations. In contrast, functionally able men had a slightly higher mean level of total cholesterol than men with impairments, which could be due to a more adequate nutrition [15]. Men were more functionally able (80%) than women (70%).…”
Section: Discussionmentioning
confidence: 84%
“…Twenty-eight percent of 2327 community living older adults in Turkey appeared to be at risk of malnutrition (score ≤ 11) in an outpatient geriatric clinic (Ülger et al, 2010). A higher prevalence of being at risk of malnutrition (70.4%) was documented in China (Ji et al, 2012), while aa Finnish study reported 15% of older adults to be either malnourished or at risk (Nykänen et al, 2013).…”
Section: Mini Nutritional Assessment-short Form (Mna-sf ® )mentioning
confidence: 95%
“…Poor self-rated health, receiving home care and meal services, polypharmacy, symptoms of depression, cognitive impairment, older age, and poor functional status were associated with an increased malnutrition risk (Nykänen et al, 2013).…”
Section: Mini Nutritional Assessment-short Form (Mna-sf ® )mentioning
confidence: 97%
See 1 more Smart Citation